Porcentagem: utilizando a ludicidade como ferramenta de ensino/aprendizagem para alunos do 6º ano do ensino fundamental - Souza, Lucas Carvalho de (Brasil, 2019)
This work of completion of the degree course in Mathematics and Physics Sciences has as general objective to stimulate in students the spontaneous and creative development of their knowledge and to allow teachers to broaden their teaching methodologies. In this way, a didactic sequence was elaborated, using a differentiated methodology with the use of playful games. The descriptive / qualitative research had its data collected through a questionnaire, informal observations through Supervised Stages, initial evaluation responses as diagnosis, students' participation in the games and response in the final evaluation as a satisfactory result of the application of this one. The theoretical referential is Significant Learning, based on the theory of fractional, interest and percentage concepts, since they are completely involved within the percentage. The experimentation of the didactic sequence happened in a school of the municipal network of the City of Coari - AM. It is noteworthy that the games used promoted a significant learning for the academics. The results prove the importance of working with play games during Mathematics classes.